Cognitive styles in admission procedures for assessing candidates of architecture. Issue 2 (17th February 2016) - Casakin, Hernan; Gigi, Ariela
Abstract : Cognitive style has a strong predictive power in academic and professional success. This study investigated the cognitive profile of candidates studying architecture. Specifically, it explored the relation between visual and verbal cognitive styles, and the performance of candidates in admission procedures. The cognitive styles of candidates who were accepted were compared with those of rejected candidates and first-year architectural students using the Visual/Semantic Cognitive-Style computerised test. Results showed that candidates with visual style achieved higher scores than candidates with semantic style. A significant difference was found for cognitive-style intensity, where visual style strength in first-year students was significantly higher than in rejected candidates, but less significant when compared to the accepted candidates. Moreover, semantic style intensity in both first-year students and accepted candidates was significantly lower than in the group of rejected candidates. The test is proposed as a reliable predictor of success in architectural studies.